Forecasting the development of the Belarusian agro-industrial complex before 2030 against the background of global agro-brands - Kovalev, Mikhail M.; Chervyakova, Evgenia A. (Journal of the Belarusian State University. Economics, 2018)
The article analyzes the current state of agriculture in the Republic of Belarus, identifies the main reasons for its low efficiency, determines the ways of its sustainable development, which can strengthen the countryʼs position in the world production of agricultural products. The trends formed in the world agricultural production and trends in the development of global markets for agricultural raw materials and food are considered. The analysis of international trade in food was carried out and priority directions of country diversification of export of agricultural products for Belarusian producers were identified. Trend and factor econometric models of forecasting the development of the domestic agrarian and food sectors of the economy up to 2030 were constructed: a change in the yield of the main agricultural crops, the production of meat and milk under the influence of global trends. The main problems of functioning and further development of the Belarusian agroindustrial complex have been revealed, ways of their solution have been suggested, including through improvement of the organizational and economic mechanisms.
Keywords: agriculture; agro-food complex; forecasting; trend and factor models; yield; production of meat and milk